Earth Science, 3rd Edition - Mark Hendrix; Graham R. Thompson (Cengage Learning, 2020)
Designed in direct response to student surveys, focus groups and interviews, Hendrix/Thompson's EARTH SCIENCE: AN INTRODUCTION, 3rd Edition, delivers concise yet comprehensive coverage in an engaging and accessible format for majors and non-majors alike. The revised text brings concepts to life with current research and examples, a new-and-improved art program, over 150 new photos, and a clean, modern design. A second-to-none supplements package equips you with a wealth of resources, including MindTap--the digital learning solution that enables you to learn on your own terms.